2021
DOI: 10.1177/09544062211037363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-yarn hybridisation and fibre architecture on the impact response of composite laminates: Experimental and numerical analysis

Abstract: Advanced composite laminates (i.e. glass composite laminates) are highly susceptible to low velocity impact, and the induced damage failures substantially reduced their residual mechanical properties and safe-service life during their application. Therefore, experiments and simulation efforts to predict their low-velocity impact damages and energy absorbing have significant importance in composite structures design. In this regards, experimental and finite element analysis (FEA) with aiding Abaqus software wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Figure 12 shows the mode-II fracture toughness values plotted against crack length. These values have been calculated by using equation (12). And the G IIc values of all samples measured at their peak forces are compared and presented in Table 4.…”
Section: Results Of Enf Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 12 shows the mode-II fracture toughness values plotted against crack length. These values have been calculated by using equation (12). And the G IIc values of all samples measured at their peak forces are compared and presented in Table 4.…”
Section: Results Of Enf Testsmentioning
confidence: 99%
“…[1][2][3] Nevertheless, these laminates are particularly prone against delamination, which strongly reduces their properties such as the load-bearing capacity, compression strength, toughness, and fatigue life. [4][5][6][7][8][9][10][11][12] Therefore, the study to enhance the interlaminar fracture toughness of glass fibre laminates has drawn the attention of the designers and composites manufacturers. Delamination or inter-ply separation is the most predominant and crucial failure mechanism in composite laminates.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researches have been conducted to investigate the impact behaviour of NCF composite. Shyr et al 29 examined the damage failure growth and failure strength of composite laminates made from cross-ply NCF, E glass woven fabric and nonwoven mat during impact tests. It was evident from the results that the NCF had higher absorption of impact energy and higher delamination than other composite laminates.…”
Section: Improving By Reinforcement Constructionmentioning
confidence: 99%
“…[12][13][14] The industrial engineers and materials scientists constantly strive to improve the impact properties and fracture toughness of fiber-reinforced composites, which still remains a key challenge. In this regard, several researches have been conducted on experimental, [15][16][17][18][19][20][21][22][23] analytical 15,[24][25][26][27][28] and computational approaches [29][30][31][32][33][34][35][36] to understand the failure behavior of fibre reinforced composites against impact loading.…”
Section: Introductionmentioning
confidence: 99%
“…11 In order to ensure that impact induced composites do not catastrophically fail during service life and maintain maximum structural efficiency, the manufacturers and designers give significant attention to the post-impact properties such as compressive and flexural properties of composite laminates. [12][13][14] Hence, it is important to understand their ability to continue functioning properly after damage events by evaluating their residual strength either compressive or flexural strength after impact tests. [15][16][17][18] Many investigations have demonstrated that the damage tolerance of composite laminates can be improved by adopting different strategies.…”
Section: Introductionmentioning
confidence: 99%